NATURAL DYEING OF WOVEN FABRICS BY THE BADUY INDIGENOUS COMMUNITY: A STUDY OF CULTURAL CONSERVATION BEHAVIOR AND MODIFICATION: Pewarnaan Alami Tenun Oleh Masyarakat Adat Baduy : Kajian Perilaku Konservasi Budaya Dan Modifikasi - Maftuhi; Adam Ardiansyah; Dandi Adhi Septian; Andi Irfanha Ardhi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The purpose of this study is to examine the cultural conservation practices of the Baduy Indigenous people and the changes they make in an attempt to preserve natural Tenun dyes. This study's methodology is qualitative and interdisciplinary, specifically cultural, and incorporates a number of ideas, including cultural conservation, conservation behavior, and adaptation. Interviews, literature reviews, and documentation served as the primary and secondary sources of the research data. According to the study's findings, the Baduy Indigenous group can gain economically and in terms of the preservation of natural biological resources by modifying natural colors. Furthermore, the community that has been successful in identifying plants with high economic potential in the Baduy environment undoubtedly benefits economically, and the benefits of conservation of natural resources include the preservation of a particular species and its habitat, which prevents damage from outside communities and tends to be beneficial and empowering for the Baduy community itself, as well as the sustainability of Baduy culture.